1990
DOI: 10.1111/j.1365-2249.1990.tb03339.x
|View full text |Cite
|
Sign up to set email alerts
|

A primed state exists in vivo following histological regression of amyloidosis

Abstract: SUMMARYUsing a sensitive, quantitative, and non-invasive in vivo method, based on the specific binding of serum amyloid P component to amyloid fibrils, we have directly documented the spontaneous resolution of A A amyloid deposits in mice, and the prolonged existence thereafter ofa primed state of enhanced susceptibility to further amyloid deposition. These results may have important implications for understanding and management of amyloidosis in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 7 publications
3
14
0
Order By: Relevance
“…That means the individuals may be primed for the amyloid disease in the case that a chronic inflammatory disease is acquired later. A similar primed state has been described in murine AA-amyloidosis after resolution of the deposits [57]. It will be very difficult to prove an association of ingestion of amyloid and development of AA-amyloidosis if this kind of delayed effect is true also in human.…”
Section: Possible Inoculation In Humansupporting
confidence: 52%
“…That means the individuals may be primed for the amyloid disease in the case that a chronic inflammatory disease is acquired later. A similar primed state has been described in murine AA-amyloidosis after resolution of the deposits [57]. It will be very difficult to prove an association of ingestion of amyloid and development of AA-amyloidosis if this kind of delayed effect is true also in human.…”
Section: Possible Inoculation In Humansupporting
confidence: 52%
“…Induction of murine AA amyloidosis by sustained chronic inflammation typically takes several weeks (7). However, mice in which AA amyloid deposits have regressed following remission of chronic inflammation are primed for rapid reaccumulation when they receive a new inflammatory stimulus (19), and previously untreated mice are readily primed by i.v. injection of amyloidotic tissue extracts or isolated amyloid fibrils, so-called amyloid enhancing factor (AEF) (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…Based on such findings, it was suggested that amyloid seeding potential is not solely based on primary structure, and that further study of the 3-D conformation of the protein is required [19]. More aggressive and severe forms of AA deposition were observed after the second inoculation, because the mice were primed after the first inoculation [7,22]. The maximal AA deposition was observed in mice receiving a second inoculation of murine AA fibrils, followed by bovine AA fibrils and lastly administration of silver nitrate alone.…”
Section: Discussionmentioning
confidence: 99%